2015
DOI: 10.1517/14712598.2015.1026804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thymosin β4 and its N-terminal fragment Ac-SDKP on TGF-β-treated human lung fibroblasts and in the mouse model of bleomycin-induced lung fibrosis

Abstract: We conclude that, compared to Tβ4, Ac-SDKP may have greater potential as an anti-fibrotic agent in the lung. Further in vivo experiments are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Convincing evidence for a direct suppressive effect of Tβ4 on the activation of HSCs comes from our in vitro experiments. The results demonstrated that Tβ4 did not significantly affect the basal expression of α‐SMA, Col1A2 or pro‐fibrotic cytokines such as TGF‐β1, PDGF‐B, CTGF and PAI‐1 in HSCs, as in the case of a previous study in which Tβ4 did not inhibit α‐SMA or Col‐I expression in fibroblasts derived from both normal lung tissue and idiopathic pulmonary fibrosis . However, Tβ4 significantly reduced the over‐expression of α‐SMA, Col1A2 and pro‐fibrotic cytokines such as TGF‐β1, PDGF‐B, CTGF and PAI‐1, as well as the phosphorylation of Smad2/3, in TGF‐β1‐stimulated HSCs, suggesting that Tβ4 is able to blunt the TGF‐β1 signaling pathway.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Convincing evidence for a direct suppressive effect of Tβ4 on the activation of HSCs comes from our in vitro experiments. The results demonstrated that Tβ4 did not significantly affect the basal expression of α‐SMA, Col1A2 or pro‐fibrotic cytokines such as TGF‐β1, PDGF‐B, CTGF and PAI‐1 in HSCs, as in the case of a previous study in which Tβ4 did not inhibit α‐SMA or Col‐I expression in fibroblasts derived from both normal lung tissue and idiopathic pulmonary fibrosis . However, Tβ4 significantly reduced the over‐expression of α‐SMA, Col1A2 and pro‐fibrotic cytokines such as TGF‐β1, PDGF‐B, CTGF and PAI‐1, as well as the phosphorylation of Smad2/3, in TGF‐β1‐stimulated HSCs, suggesting that Tβ4 is able to blunt the TGF‐β1 signaling pathway.…”
Section: Discussionsupporting
confidence: 48%
“…Error bars indicate the SEM Tβ4 did not inhibit α-SMA or Col-I expression in fibroblasts derived from both normal lung tissue and idiopathic pulmonary fibrosis. 33 However, Tβ4 significantly reduced the over-expression of α-SMA, Col1A2 and pro-fibrotic cytokines such as TGF-β1, PDGF-B, CTGF and PAI-1, as well as the phosphorylation of Smad2/3, in TGF-β1stimulated HSCs, suggesting that Tβ4 is able to blunt the TGF-β1 signaling pathway.…”
Section: Discussionmentioning
confidence: 90%
“…Previously we showed anti-fibrotic properties of Ac-SDKP in vitro , differently to its precursor Tβ4 [16]. On the other hand, we demonstrated that Tβ4 was unable to prevent established pulmonary fibrosis at 14 and 21 days in BLEO-treated mice, in contrast to its protective role at 7 days [17].…”
Section: Discussionmentioning
confidence: 88%
“…Amplification conditions were identical for all genes: 94°C, 5 min and 45 cycles of 2 steps: 95°C, 15 sec and 60°C, 30 sec. Relative quantification of target gene levels was performed by comparing ΔCt as described elsewhere [15, 16], and calculating ΔΔCt with the values from the Sham as the calibrator.…”
Section: Methodsmentioning
confidence: 99%
“…However, protective effects of TB4 on organ injury and fibrosis have been investigated by many other previous studies 28, 30, 31, 6467 . Conte E. et al .…”
Section: Discussionmentioning
confidence: 99%